2014
DOI: 10.1002/cctc.201300844
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Boosts Ring‐Opening Activity of Iridium

Abstract: A variety of bimetallic Ni–Ir catalysts were synthesised by preforming nanoparticles in the presence of polyvinylpyrrolidone, followed by deposition on γ‐alumina and high‐temperature polymer removal. The Ni–Ir (1:1 molar ratio) nanoparticles prepared by the hydrogen‐sacrificial technique (Ir reduction on the preformed Ni nanoparticles with surface Ni hydride) allowed increasing indane ring opening activity per total amount of Ir as compared to monometallic Ir. The simultaneous reduction of Ni and Ir precursors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 67 publications
(94 reference statements)
0
7
0
Order By: Relevance
“…As the chemical economy gradually shifts from fossil fuels to renewable resources, it becomes important to develop technologies to upgrade renewable platform molecules to final products of industrial relevance. Renewable heterocyclic molecules 5-hydroxymethylfurfural and furfural can be produced in high yields by depolymerizing and dehydrating lignocellulosic biomass. , Hydrogenolysis of these heterocyclics has been shown to be a viable route toward the production of long-chain hydrocarbons, alcohols, and polyols. Selective hydrogenolysis of furfural at the C–O bond(s) in the aromatic ring with an iridium catalyst has been shown to be effective in the production of 1,5-pentanediol (1,5-PeD), a valuable precursor for the production of polyesters and polyurethanes. , While the hydrogenolysis of furfural to 1,5-PeD has been known for decades, whether the reaction proceeds through the full saturation of the aromatic ring , remains a controversial topic. Recent experiments have indicated that the hydrogenolysis of unsaturated homo- and heterocyclics is more facile over that of their saturated equivalents.…”
Section: Introductionmentioning
confidence: 99%
“…As the chemical economy gradually shifts from fossil fuels to renewable resources, it becomes important to develop technologies to upgrade renewable platform molecules to final products of industrial relevance. Renewable heterocyclic molecules 5-hydroxymethylfurfural and furfural can be produced in high yields by depolymerizing and dehydrating lignocellulosic biomass. , Hydrogenolysis of these heterocyclics has been shown to be a viable route toward the production of long-chain hydrocarbons, alcohols, and polyols. Selective hydrogenolysis of furfural at the C–O bond(s) in the aromatic ring with an iridium catalyst has been shown to be effective in the production of 1,5-pentanediol (1,5-PeD), a valuable precursor for the production of polyesters and polyurethanes. , While the hydrogenolysis of furfural to 1,5-PeD has been known for decades, whether the reaction proceeds through the full saturation of the aromatic ring , remains a controversial topic. Recent experiments have indicated that the hydrogenolysis of unsaturated homo- and heterocyclics is more facile over that of their saturated equivalents.…”
Section: Introductionmentioning
confidence: 99%
“…S10b †). 45,46 The band at 2007 cm À1 can be ascribed to linear CO adsorption on metallic Ir (Fig. S10a †).…”
Section: Resultsmentioning
confidence: 99%
“…Transition metal catalysts can open naphthenic ring compounds when the metal ensembles possess hydrogenolysis activity, 91 for example Pt/Al 2 O 3 , Ir/Al 2 O 3 , Ir/SiO 2 , Pt–Ir/Al 2 O 3 , Pt–Ir/SiO 2 , Ru–Pd/Al 2 O 3 , Ru–Ir/Al 2 O 3 and Ni–Ir/Al 2 O 3 . 12,89,92–94 Ring opening is proposed to occur via hydrogenolysis of endocyclic C–C bonds bound to metal sites in three different coordination modes (dicarbene, π-adsorbed olefin or metallocyclobutane) as illustrated in Scheme 3a–c. 63 The selectivity and distribution of ring opening products will depend on which of these intermediates is formed.…”
Section: Selective Ring Opening Catalystsmentioning
confidence: 99%